2021
DOI: 10.3389/fphys.2021.708824
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Placental Extracellular Vesicles-Associated Fas Ligand and TNF-Related Apoptosis-Inducing Ligand in Pregnancies Complicated by Early and Late Onset Preeclampsia

Abstract: Preeclampsia (PE) is a hypertensive disorder that affects 2–8% of pregnancies and is one of the main causes of fetal, neonatal, and maternal mortality and morbidity worldwide. Although PE etiology and pathophysiology remain unknown, there is evidence that the hyperactivation of maternal immunity cells against placental cells triggers trophoblast cell apoptosis and death. It has also been reported that placenta-derived extracellular vesicles (EV) carry Fas ligand (FasL) and Tumor necrosis factor-related apoptos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…Increased syncytiotrophoblast release of extracellular vesicles (Fig. 2b) into the maternal circulation is found in pre-eclampsia [191][192][193] . These extracellular vesicles are enriched in anti-angiogenic factors, apoptosis-inducing ligands and active caspase 3, especially in early-onset pre-eclampsia 192,193 .…”
Section: Dysregulated Placental Release Of Factorsmentioning
confidence: 99%
“…Increased syncytiotrophoblast release of extracellular vesicles (Fig. 2b) into the maternal circulation is found in pre-eclampsia [191][192][193] . These extracellular vesicles are enriched in anti-angiogenic factors, apoptosis-inducing ligands and active caspase 3, especially in early-onset pre-eclampsia 192,193 .…”
Section: Dysregulated Placental Release Of Factorsmentioning
confidence: 99%
“…Furthermore, it has been reported that placental-derived exosomes can suppress certain immune responses through increasing lymphocyte apoptosis and reducing CD3 expression [ 61 ]. It has also been found that exosomes can regulate the NKG2D receptor on NK, CD8(+), and gamma delta T cells, which has resulted in a reduction of cytotoxicity in vitro [ 61 ].…”
Section: Exosomes As Therapeutic Tools In Reproductive Pathologymentioning
confidence: 99%
“…Furthermore, it has been reported that placental-derived exosomes can suppress certain immune responses through increasing lymphocyte apoptosis and reducing CD3 expression [ 61 ]. It has also been found that exosomes can regulate the NKG2D receptor on NK, CD8(+), and gamma delta T cells, which has resulted in a reduction of cytotoxicity in vitro [ 61 ]. The clinical applicability of exosomes can therefore relate to their utilisation to treat a multitude of disorders during pregnancy, including impaired foetal growth and inflammation (refer to Tables 2 and 3 for a summary).…”
Section: Exosomes As Therapeutic Tools In Reproductive Pathologymentioning
confidence: 99%
“…Moreover, the repertoire of cargo molecules in circulating sEVs of women with preeclampsia also changes, with augmented Flt‐1, IL‐2, and TNF‐α and reduced IL‐10, suggesting an acquired proinflammatory, Th1‐biased phenotype 216,218 . This is also accompanied by increased TRAIL and Fas‐L in sEVs released by placenta explants from early‐onset, but not late‐onset preeclampsia 219 . Preeclampsia‐related sEVs change the cytokine repertoire of the BeWo trophoblast line, with increased IL‐8 and decreased IL‐10.…”
Section: Evs' Modulated Immunity In Gestational Diseasesmentioning
confidence: 99%
“…216,218 This is also accompanied by increased TRAIL and Fas-L in sEVs released by placenta explants from earlyonset, but not late-onset preeclampsia. 219 Preeclampsia-related sEVs change the cytokine repertoire of the BeWo trophoblast line, with increased IL-8 and decreased IL-10.. 220 Similarly, the miRNA cargo repertoire of these sEVs is different. 217,221 Functionally, these changes have been associated with defective angiogenesis, altered vascular smooth muscle migration, increased vascular tone, and increased platelet activation.…”
Section: Preeclampsia and Fetal Growth Restrictionmentioning
confidence: 99%